Perancangan UI/UX Aplikasi Mobile Untuk Meningkatkan Efisiesi Pembayaran Air Perumda Tirta Musi Menggunakan Metode Design Thinking - Aldino Putra Noveni; Dinna Yunika Hardiyanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Perumda Tirta Musi is a regional company that provides clean water services to the people of Palembang City and its surrounding areas. However, the current payment system is still dominated by conventional methods, such as payments at branch offices or through third-party payment counters, which are considered inefficient. To address this issue, this study aims to design the user interface (UI) and user experience (UX) of the Perumda Tirta Musi mobile water payment application using the Design Thinking approach. This method is applied to produce a design that is more effective and efficient in meeting user needs. Additionally, usability evaluation was conducted using the System Usability Scale (SUS) method to assess the quality of the interface and user experience. The study results show that the Perumda Tirta Musi mobile water payment application achieved an average usability score of 90.5, which is above the average score of 68. This score places the application in Grade A with an Excellent rating. With a high level of usability, the application enables users to complete tasks faster, reduce errors, and enhance user satisfaction and loyalty. The implementation of this application is expected to improve the efficiency of the payment process and enhance the quality of Perumda Tirta Musi's services.